Integration of metabolomics and transcriptomics provides insights into enhanced osteogenesis in Ano5Cys360Tyr knock-in mouse model - Li, Hongyu; Liu, Sirui; Miao, Congcong; Lv, Yan; Hu, Ying (Frontiers in Endocrinology, 2023)
Gnathodiaphyseal dysplasia (GDD; OMIM#166260) is a rare autosomal dominant disorder characterized by diaphyseal sclerosis of tubular bones and cemento-osseous lesions in mandibles. GDD is caused by point mutations in the ANO5 gene. However, the mechanisms underlying GDD have not been disclosed. We previously generated the first knock-in mouse model for GDD expressing a human mutation (p.Cys360Tyr) in ANO5 and homozygous Ano5 knock-in (Ano5KI/KI) mice exhibited representative traits of human GDD especially including enhanced osteogenesis. Here, metabolomics and transcriptomics analyses were conducted for wildtype (Ano5+/+) and Ano5KI/KI mature mouse calvarial osteoblasts (mCOBs) grown in osteogenic cultures for 14 days to identify differential intracellular metabolites and genes involved in GDD. Metabolomics identified 42 differential metabolites that are primarily involved in amino acid and pyrimidine metabolism, and endocrine and other factor-regulated calcium reabsorption. Concomitantly, transcriptomic analysis revealed 407 differentially expressed genes in Ano5KI/KI osteoblasts compared with wildtype. Gene ontology and pathway analysis indicated that Ano5Cys360Tyr mutation considerably promoted cell cycle progression and perturbed calcium signaling pathway, which were confirmed by validated experiments. qRT-PCR and CCK-8 assays manifested that proliferation of Ano5KI/KI mCOBs was enhanced and the expression of cell cycle regulating genes (Mki67, Ccnb1, and Ccna2) was increased. In addition, SEM-EDS demonstrated that Ano5KI/KI mCOBs developed higher calcium contents in mineral nodules than Ano5+/+ mCOBs, while some calcium-related genes (Cacna1, Slc8a1, and Cyp27b1) were significantly up-regulated. Furthermore, osteocalcin which has been proved to be an osteoblast-derived metabolic hormone was upregulated in Ano5KI/KI osteoblast cultures. In summary, our data demonstrated that the Ano5Cys360Tyr mutation could affect the metabolism of osteoblasts, leading to unwonted calcium homeostasis and cellular proliferation that can contribute to the underlying pathogenesis of GDD disorders.